Efektivitas Pelatihan Konselor Sebaya Terhadap Peningkatan Pengetahuan dan Keterampilan Siswa dalam Memberikan Dukungan Sebaya di SMKN 1 Sewon - Galang Rambu Anarki (Ikatan Dai Indonesia, 2025)
Adolescence is a critical developmental stage marked by emotional instability and vulnerability to risky behaviors. Many students face challenges such as academic decline, truancy, family problems, and even involvement in delinquent acts, which can negatively impact their mental health. This study aimed to implement and evaluate a peer counselor training program at SMKN 1 Sewon to enhance students’ knowledge and skills in providing peer support. Using a pretest-posttest design and qualitative observation, 50 students participated in the intervention. The Wilcoxon Signed Ranks Test showed a significant increase in knowledge after training (Z = -5.887, p < 0.001), with the posttest mean score (M = 10.84) higher than the pretest (M = 7.42). Qualitative findings also revealed positive responses from participants, who reported improved confidence, empathy, and counseling skills. Peer counselor training is thus proven to be effective in promoting mental health literacy and preventive efforts among adolescents in the school environment.